4Ps a workshop on preeclampsia, postpartum hemorrhage and preterm labor prevention for the midwives and general physicians - Olivar, Joseph U.
The blended workshop on risk assessment and preventive strategies, timely referral, and patient education for midwives can be a valuable initiative in addressing maternal and neonatal health challenges in the Philippines. Through a comprehensive approach that combined asynchronous learning with focused group discussions, the workshop aimed to empower frontline healthcare providers with the necessary skills and knowledge to mitigate the incidence and severity of maternal and neonatal complications, such as postpartum hemorrhage, preeclampsia, and preterm birth.